Guardians of opportunity: emerging health technology assessment in Brazil, South Korea and Taiwan. Issue 3 (24th May 2013) - Beckerman, Rachel; Chowdhury, Cyrus A.; Park, Shinkyu
Abstract When considering their health technology assessment (HTA) submission strategy, pharmaceutical manufacturers have traditionally focused on catering to the demands of agencies in developed markets: the requirements of the National Institute for Health and Care Excellence (NICE) in the UK, Common Drug Review (CDR) in Canada and Pharmaceutical Benefits Advisory Committee (PBAC) in Australia are familiar to many. However, in strategically important emerging markets such as Brazil, South Korea and Taiwan manufacturers' HTA submissions are becoming increasingly critical pivots for determining access to the presumed commercial opportunity inherent in these markets. Often, these markets serve as regional bellwethers, blueprinting consequences of a local negative HTA decision for high‐opportunity neighbouring markets. What types of evidence are required by these 'guardians of opportunity' and how can manufacturers achieve their successful recommendation? How can HTA submissions to the Health Insurance Review Agency (HIRA; South Korea), Comissão Nacional de Incorporação de Tecnologias no Sistema Único de Saúde (CONITEC; Brazil) and Centre for Drug Evaluation (CDE)/Bureau for National Health Insurance (BNHI; Taiwan) be optimised in the context of a global HTA strategy?